Community Health Workers Can Provide Psychosocial Support to the People During COVID-19 and Beyond in Low- and Middle- Income Countries - Sabuj Kanti Mistry; Sabuj Kanti Mistry; Ben Harris-Roxas; Uday Narayan Yadav; Sadia Shabnam; Lal Bahadur Rawal; Mark F. Harris (Frontiers Media S.A., 2021)
The COVID-19 pandemic has been the most challenging public health issue which not only affected the physical health of the global population but also aggravated the mental health conditions such as stress, anxiety, fear, depression and anger. While mental health services are seriously hampered amid this COVID-19 pandemic, health services, particularly those of Low- and Middle- Income Countries (LMICs) are looking for alternatives to provide psychosocial support to the people amid this COVID-19 and beyond. Community Health Workers (CHWs) are an integral part of the health systems in many LMICs and played significant roles such as health education, contact tracing, isolation and mobilization during past emergencies and amid COVID-19 in many LMICs. However, despite their potentials in providing psychosocial support to the people amid this COVID-19 pandemic, they have been underutilized in most health systems in LMICs. The CHWs can be effectively engaged to provide psychosocial support at the community level. Engaging them can also be cost-saving as they are already in place and may cost less compared to other health professionals. However, they need training and supervision and their safety and security needs to be protected during this COVID-19. While many LMICs have mental health policies but their enactment is limited due to the fragility of health systems and limited health care resources. CHWs can contribute in this regard and help to address the psychosocial vulnerabilities of affected population in LMICs during COVID-19 and beyond.